2019
DOI: 10.3390/nu11061282
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Oligosaccharides in the Milk of Mothers Delivering Term versus Preterm Infants

Abstract: Human milk oligosaccharides (HMOs) are a major component of human milk, and play an important role in protecting the infant from infections. Preterm infants are particularly vulnerable, but have improved outcomes if fed with human milk. This study aimed to determine if the HMO composition of preterm milk differed from that of term milk at equivalent stage of lactation and equivalent postmenstrual age. In all, 22 HMOs were analyzed in 500 samples of milk from 25 mothers breastfeeding very preterm infants (< … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
125
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(137 citation statements)
references
References 56 publications
10
125
2
Order By: Relevance
“…There are several studies reporting that Secretor-status and Lewis type can determine fucosylation patterns [15]. FUT2 encoded by the Secretor gene determines the presence of α1,2-fucosylated HMOs such as 2 -FL and LNFP-I, and FUT3 encoded by the Lewis gene synthesizes α1,4-fucosylated HMOs such as LNFP-II and Lacto-N-difucohexaose (LNDFH) [15][16][17]. Other FUTs determined the presence of α1,3-fucosylated HMOs such as 3 -FL and LNFP-IV, whose synthesis was not influenced by the Se or Le genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies reporting that Secretor-status and Lewis type can determine fucosylation patterns [15]. FUT2 encoded by the Secretor gene determines the presence of α1,2-fucosylated HMOs such as 2 -FL and LNFP-I, and FUT3 encoded by the Lewis gene synthesizes α1,4-fucosylated HMOs such as LNFP-II and Lacto-N-difucohexaose (LNDFH) [15][16][17]. Other FUTs determined the presence of α1,3-fucosylated HMOs such as 3 -FL and LNFP-IV, whose synthesis was not influenced by the Se or Le genes.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond genetic factors, several studies reported that HMOs composition varied with lactation stage [11,15,17,[20][21][22][23][24][25][26]. However, most studies collected samples in a single time point or focused on first few weeks of lactation.…”
Section: Introductionmentioning
confidence: 99%
“…, and lipid (g•kg −1 •d −1 ) intake were calculated including milk content and the amount of HMF as well as the parenterally administered macronutrients. Lactose intake was calculated from the total carbohydrates measured in OMM assuming a 20% of total carbohydrates as non-metabolized oligosaccharides [29][30][31][32][33][34][35]. Energy intake was calculated from the macronutrient concentrations by using the Atwater factors: 9 kcal/g for fat and 4 kcal/g for protein and estimated lactose.…”
Section: Data Collectionmentioning
confidence: 99%
“…Authors enhance the importance of passive immunisation through mothers' antibodies transfer from breast milk, which has a key role for infant immune protection in the first months [9]. Differences in oligosaccharides content between term and preterm milk have also been examined in view of the potential implications for preterm infants' clinical outcomes with special regard to their increased vulnerability to infections [10]. Given the widely known anti-inflammatory and antimicrobial properties of human milk, authors have also explored its implementation as a powerful therapeutic agent for skin issues, suggesting its potential use in settings with limited access to medicine [11].…”
mentioning
confidence: 99%
“…Benefits of human milk feeding are indeed even more critical among specific populations at high risk of developing adverse outcomes, as preterm infants [22]. This value is highlighted not only by the positive effects that human milk has in modulating preterms' outcomes at every level but also by the results of studies in this issue demonstrating the higher levels of bioactive, micro and macronutrient contents in preterm milk, compared to full-term [10,[23][24][25][26]. Within this context, however, authors have underlined the potential lack of mineral content of preterm milk that should be taken into consideration in the approach to the fortification of milk for the preterm population [27].…”
mentioning
confidence: 99%